BS EN IEC 60512-99-003. Connectors for electrical and electronic equipment. Tests and measurements. Part 99-003. Endurance test schedules. Test 99c: Test schedule for balanced single-pair connectors unmating under electrical load (4th May 2022) - British Standards Institution
No abstract available